2001
DOI: 10.1063/1.1342046
|View full text |Cite
|
Sign up to set email alerts
|

Nanofractography of shocked RDX explosive crystals with atomic force microscopy

Abstract: Examination with atomic force microscopy has revealed apparent shear-type cleavage steps with heights as small as 0.05 nm, smaller than the size of cyclotrimethylenetrintramine (RDX) molecules, on the fracture surfaces of crystals that were subjected to aquarium shocks of 61.6 or 129 kbar, both greater than the pressure (38 kbar) required for the alpha-to-gamma phase transformation. The shocked centimeter size, originally transparent crystals became opaque and white from prolific fractures and internal cracks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Mechanically enhanced chemistry [1] is observed during indentation [2], friction [3], shock and detonation [4 -11] of energetic materials [12 -14]. A major unsolved problem in this area of mechanochemistry is how strains trigger chemical reactions that cause detonation.…”
mentioning
confidence: 99%
“…Mechanically enhanced chemistry [1] is observed during indentation [2], friction [3], shock and detonation [4 -11] of energetic materials [12 -14]. A major unsolved problem in this area of mechanochemistry is how strains trigger chemical reactions that cause detonation.…”
mentioning
confidence: 99%
“…Such observation was made for cleavage step heights on shocked RDX crystals by Sharma et al [26] Here, we suggest that such smaller step heights might be accounted for by partial dislocation Burgers vectors that penetrate the cleavage surface or by only a component of the actual unit dislocation Burgers vector being normal to the cleavage plane. The observation is important in understanding the influence of mechanical forces on the detonation of energetic materials, because such liberated energy comes from intramolecular decomposition, not from fracturing of the weaker molecular crystal bonds.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies of cyclotrimethylenetrinitramine (RDX) crystals grown during high acceleration (200,000 g) in an ultracentrifuge have been reported. [1,2] The AFM studies have shown that these RDX crystals have fewer defects than RDX crystals grown at 1 g [3,4] and therefore should be less sensitive to mechanical shock.…”
Section: Introductionmentioning
confidence: 99%
“…This may cause even stronger distortion of some of the atomic bonds located in this region and the appearance of a significant number of additional bonding and antibonding states in the RDX band gap. An extensive body of dislocation analysis in a variety of materials has been performed over the years by Armstrong and Elban [14,103,104]; in particular, they demonstrated an interesting contrast in the mechanical properties of molecularly bonded energetic crystals containing dislocations: the crystals are elastically soft, plastically hard, and brittle. They also show that the generation of dislocation clusters at large shock pressures plays an important role similar to the role of anharmonic lattice strains at the dislocation coresthey generate either "in situ" hot spot heating or direct electronic excitation [105].…”
Section: The Electronic Structure Of Rdx Crystals Containing Edge Dismentioning
confidence: 99%